Microstructure and Mechanical Properties of Aluminum Alloy/Stainless Steel Dissimilar Ring Joint Welded by Inertia Friction Welding - Qin, Feng; Zhang, Chunbo; Zhou, Jun; Xu, Kai; Wang, Qi; Li, Yunlei; Zhang, Wenhan (Frontiers in Materials, 2022)
In recent years, studying the weldability of dissimilar metal composite structure has been a research hotspot, with the potential to make full use of their unique benefits. In this article, inertia friction welding was utilized to join Φ130 forged ring of 2219 aluminum alloy with 304 stainless steel. EBSD and SEM were utilized to examine the joint microstructure in depth. Depending on the research, a significant thermal-mechanical coupling effect occurs during welding, resulting in inadequate recrystallization on aluminum side TMAZ and forming zonal features. The crystal orientation and grain size of each TMAZ region reflects distinctly differences. On joint faying surface, growth of IMCs was inhibited by fast cooling rate and mechanical and metallurgical bonding Characteristics were found depended on discontinuous distribution of IMCs. The joint tensile strength can reach 169MPa achieved 96% of 2219-O, fracture occurs on aluminum side base metal presenting ductile fracture characteristic.